BENTUK DAN FUNGSI DRAMA TARI GANDRUNG TERAKOTA DI KABUPATEN BANYUWANGI - Sugiharta, Hiltania Milyadita (Institut Seni Indonesia Surakarta, 2023)
One form of the existence of performing arts in Banyuwangi Regency is the Gandrung dance. In its development, various Gandrung dances emerged with various performances. The Gandrung Terrakota dance drama is one of the performing arts that is developing in Banyuwangi Regency. This performance combines drama and dance performances which are performed in groups using a story line with the theme of the history of the journey of a Gandrung dancer. The Gandrung Terrakota dance drama performance form in Banyuwangi Regency was created in 2018 by Mr. Slamet Dihardjo, as a teacher from SMK Negeri 1 Banyuwangi, Dance Department. He, together with the students of SMK Negeri 1 Banyuwangi, Department of Dance, created a work that depicts the journey of a Gandrung dancer to the graduation ritual process of a Gandrung dancer and is ready to perform in full. This study aims to describe the formulation of the problems related to the Gandrung Terakota Dance drama, including: (1) how is the form of the Gandrung Terakota Dance drama; and (2) how is the function of the Gandrung Terakota Dance drama. Both of these problems use qualitative research methods that examine textual and contextual performing arts. There are two stages that must be carried out in qualitative research, namely the data collection stage which consists of observation, interviews and research. The second stage is the data processing stage which is carried out by analyzing the data according to the Gandrung Terakota Dance drama. The research results show that the Gandrung Terakota Dance drama is a form of performance which has 5 scenes packaged into the Gandrung Terakota Dance drama performance. The function of this drama is classified as a function of ritual, entertainment, and spectacle.